Memaknai Turunnya Skor Indeks Persepsi Korupsi Indonesia Tahun 2020 - Suyatmiko, Wawan Heru (Integritas : Jurnal Antikorupsi, 2021)
Corruption, pandemic, democracy and investment are factors reflected in the Corruption Perceptions Index score for 2020. The relations between Covid-19 pandemic handling and corruption; political integrity and democracy in the policy-making process to making important political decisions that have the potential to create political corruption; up to the risk of corruption in the problem of ease of doing business during the Covid-19 pandemic handling and the economic recovery which at the same time saw a number of business processes being trimmed and the potential for recentralization; is the portrayed in the Corruption Perception Index 2020. The drop in Indonesia's Corruption Perceptions Index score in 2020 to 37 indicates that there are still far away efforts to eradicate corruption in the midst of a pandemic situation that has hit with shared aspirations and hopes.